Intensi Berwirausaha Pada Mahasiswa Tingkat Akhir - Reny Yuniasanti; Metty Verasari (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2015)
The purpose of this research was to explore the level of entrepreneur intention of undergraduate student in Yogyakarta university. There were many factor of entrepreneur intention such as environtment, relatives, education, personality trait, age, and sex. The subjects were 100 university student who almost finished their study. The data were collected by entrepreneur intention scale. The result indicated that only 31 university student in this research have high level of entrepreneur intention (31%) . The rest, 39 student (39%) at medium level, and 30 student at low level of entrepreneur intention. Keywords: entrepreneurship, intention, university student,